2011
DOI: 10.1182/blood-2011-01-328476
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell–derived factor-1 and hematopoietic cell homing in an adult zebrafish model of hematopoietic cell transplantation

Abstract: In mammals, stromal cell-derived factor-1 (SDF-1) promotes hematopoietic cell mobilization and migration. Although the zebrafish, Danio rerio, is an emerging model for studying hematopoietic cell transplantation (HCT), the role of SDF-1 in the adult zebrafish has yet to be determined. We sought to characterize sdf-1 expression and function in the adult zebrafish in the context of HCT. In situ hybridization of adult zebrafish organs shows sdf-1 expression in kidney tubules, gills, and skin. Radiation up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
(49 reference statements)
1
34
0
Order By: Relevance
“…To further understand the interaction of HSPCs with the perivascular niche, we identified a cxcl12a:DsRed2 transgenic line that allowed us to observe mesenchymal stromal cells in the CHT (Glass et al, 2011). These are likely the “fibroblastic reticular cells” that were previously described in the CHT (Murayama et al, 2006) and similar to the “CXCL12-abundant reticular” cells in the perivascular bone marrow niche (Sugiyama et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the interaction of HSPCs with the perivascular niche, we identified a cxcl12a:DsRed2 transgenic line that allowed us to observe mesenchymal stromal cells in the CHT (Glass et al, 2011). These are likely the “fibroblastic reticular cells” that were previously described in the CHT (Murayama et al, 2006) and similar to the “CXCL12-abundant reticular” cells in the perivascular bone marrow niche (Sugiyama et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…S3A-CЈ), which is expressed in the epicardial cells (Perner et al, 2007). We did not detect expression of the cxcl12a-DsRed2 reporter (Glass et al, 2011) in MHCpositive CMs (supplementary material Fig. S3D-F) or in fli1-EGFP-positive endothelial cells (supplementary material Fig.…”
Section: Cms Express Cxcr4bmentioning
confidence: 94%
“…We first tested whether FC131, a recently developed selective CXCR4 antagonist (Narumi et al, 2010), can block zebrafish Cxcr4 function. AMD3100, a widely used CXCR4 antagonist, was not used because our previous studies indicated that it did not efficiently block Cxcr4 function, either in the adult zebrafish hematopoietic system in vivo (Glass et al, 2011) or in the migration of primordial germ cells in zebrafish embryos (data not shown). Treating zebrafish embryos with FC131 significantly impaired directed migration of primordial germ cells into the gonad-forming region (supplementary material Fig.…”
Section: Cxcr4 Function Is Required For Heart Regenerationmentioning
confidence: 99%
“…There is recent evidence that many cytokines and chemokines are similar between zebrafish and that of mammals such as CXCL12, and that the hematopoietic role of the CXCR4-CXCL12 axis in zebrafish mirrors the functional role of CXCR4-CXCL12 in mammals (17). We therefore sought to develop a zebrafish model for assessment of tumor cell homing and metastasis to the BM by injecting either MM cell lines or patient-derived MM cells into zebrafish embryos and demonstrating their homing to the caudal hematopoietic tissue (CHT) where the HSCs migrate after their emergence from the ventral wall of the dorsal aorta: (18) This posterior/caudal area is considered an early site of definitive hematopoiesis analogous to the mammalian fetal liver (19).…”
Section: Introductionmentioning
confidence: 99%